Health Profession Education Students’ Satisfaction toward Online Courses during the COVID-19 Pandemic - Soemantri, Diantha; Salsabila, Zhafirah; Yorasaki, Vernonia (UI Scholars Hub, 2023)
Background: Given the extensive use of e-learning, especially during the COVID-19 pandemic, a validated instrument is deemed important for continuous evaluation. This study aimed to measure health profession education students’ satisfaction toward the e-learning process within all health sciences cluster (HSC) courses, following further validation of the satisfaction scale for the e-learning process. Methods: A cross-sectional study using an exploratory factor analysis (EFA) was conducted to validate the 29-item Indonesian version of the satisfaction scale for the e-learning process. That the validated tool was used to measure 2,471 students’ satisfaction toward the e-learning process. Results: The EFA resulted in 19 items divided into three subscales: the teaching process (5 items), the instructional content (4 items), and the interaction and evaluation (10 items). The scores of students’ satisfaction toward the e-learning process are at 84–94% of the possible maximum score of the whole instrument or each subscale. Conclusions: The Indonesian version of the satisfaction scale for the e-learning process serves as a valid tool to measure students’ satisfaction toward e-learning. Current students have relatively good perceptions toward e-learning used in all HSC courses, including the interaction domain, which is an important aspect in an e-learning system. Strategies are warranted to maintain and further improve the e-learning process.